Performing identity through the Klong Yao tradition among the Siamese community of Perlis, Malaysia / Chayuti Tassanawongwara - Chayuti , Tassanawongwara (2018)
The long drum, the Klong Yao performances are found around the northern states of Malaysia where there are Siamese communities. Although the Siamese in Perlis is a minority group, they have succeeded in establishing the Klong Yao as a Siamese tradition. Thus, the Klong Yao tradition becomes representative of the Siamese image in the eyes of others. This study explores the presentation and representation of the Klong Yao tradition of the Siamese in the state of Perlis, Malaysia. The whole performance process makes (or shape) the identity of the community. However, the process and also the identity are facing issues and challenges. This study connects and analyzes the relations between Thai and Siamese as well as with other communities through the lenses of the Klong Yao performance. This study analyzes the construction of the identity through the performance of the Klong Yao performance and investigates how the Siamese maintained the tradition and identity through the performance process. This is a qualitative study. It relies on both primary and secondary data. Library research was conducted to collect data on the historical background of the issue. In the field, non-participant observation was conducted to observe the Siamese life in a diverse context. Also, participant observation was conducted to collect data of the Klong Yao tradition, rituals, traditional practices and ceremonies, as well as any processes concerning performing identity, are involved in this aspect. Moreover, interviews are also conducted to validate the data and collected information from library research and participant observation. The main findings of the study present performance process framework modelled on Richard Schechner‘s framework shows cultural identity formed through the Klong Yao tradition. Performance process associated with this study to point out that the Siamese protects their selfness (or their rights) against the hegemony of difference. By representing Thai-ness, Thai language particularly central-Thai dialect and Buddhist practice are crucially brought up to the Klong Yao performance. In addition, the performance process is constructed by presenting as Thai through costumes, songs and lyrics, procession and even dance. The study also shows that the Siamese community maintains the Klong Yao as well as sustains its identity by strengthening the cultural identity among the members of family, community, either throughout their villages or the state itself. Among the Siamese, the Klong Yao performance is accepted as the sharing the heritage of Thai race while among other people. It is also perceived as performing the tradition of Siamese.